Mangroves are Machines: Ecolinguistics Study - Wardana, Muhammad Kiki; Widayati, Dwi; Mulyadi, Mulyadi; Zein, T. Thyrhaya (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This study explores the conceptual metaphor of